PENINGKATAN KEMAMPUAN BERPIKIR KREATIF MATEMATIS DAN SELF-REGULATED LEARNING SISWA SMP DENGAN MENGGUNAKAN ACCELERATED LEARNING - Khoerunnisa, Nurmalita (2016)
Mathematical creative thinking is one of the ability on KTSP 2006 curriculum that students need to have. But in the reality the lack of mathematical creative thinking is still found on many students with less positive response when the students are given a non-routine problem. The purpose of this study is 1) determine whether the improvement of students' mathematical creative thinking who used Accelerated Learning is better than the students who used conventional learning; 2) determine whether the improvement of students' mathematical creative thinking who used Accelerated Learning is better than the students who used conventional learning based on their mathematical early ability (High, moderate, low); 3) determine whether the improvement of students' self-regulated learning who used Accelerated Learning is better than the students who used conventional learning; 4) determine whether the improvement of student' self-regulated learning who used Accelerated Learning is better than the students who used conventional learning based on their mathematical early ability (High, moderate, low) The method in this study was quasi-experimental. The result of this study is 1) for overall the improvement of mathematical creative thinking of students who used Accelerated Learning is better than the students who used conventional learning; 2) the improvement of mathematical creative thinking of students who used Accelerated Learning is better than the students who used conventional learning on moderate and low KAM category, while on high KAM category the improvement of students' mathematical creative thinking is not better significantly than the students who used conventional learning; 3) for overall the improvement of students' self-regulated who used Accelerated Learning is better than the students who used conventional learning; 4) the improvement of students' self-regulated who used Accelerated Learning is better than the students who used conventional learning on moderate, high and low KAM category ;---Kemampuan berpikir kreatif matematis merupakan salah satu kemampuan yang harus dimiliki siswa hal ini tercantum dalam kurikulum KTSP 2006. Namun masih banyak didapati kemampuan berpikir kreatif matematis siswa masih rendah dengan respon yang kurang positif masih selalu muncul bila siswa diberi masalah yang non rutin. Tujuan penelitian adalah 1) mengetahui apakah peningkatan kemampuan berpikir kreatif matematis siswa yang memperoleh pembelajaran Accelerated Learning lebih baik daripada siswa yang menggunakan pembelajaran konvensional; 2) mengetahui apakah apakah peningkatan kemampuan berpikir kreatif matematis siswa yang memperoleh pembelajaran Accelerated Learning lebih baik daripada siswa yang menggunakan pembelajaran konvensional ditinjau dari kemampuan awal matematis (Tinggi, Sedang, Rendah) 3) mengetahui apakah peningkatan kemampuan self-regulated learning siswa yang memperoleh pembelajaran Accelerated Learning lebih baik daripada siswa yang menggunakan pembelajaran konvensional; 4) mengetahui apakah peningkatan kemampuan self-regulated learning siswa yang memperoleh pembelajaran Accelerated Learning lebih baik daripada siswa yang menggunakan pembelajaran konvensional ditinjau dari kemampuan awal matematis (Tinggi, Sedang, Rendah) Metode penelitian dalam penelitian ini adalah kuasi eksperimen. Kesimpulan penelitian adalah 1) Peningkatan kemampuan berpikir kreatif matematis siswa yang mendapat pembelajaran dengan Accelerated Learning lebih baik daripada yang memperoleh pembelajaran konvensional jika ditinjau secara keseluruhan; 2) Peningkatan kemampuan berpikir kreatif matematis siswa yang mendapat pembelajaran dengan Accelerated Learning lebih baik daripada peningkatan kemampuan berpikir kreatif matematis siswa yang memperoleh pembelajaran konvensional pada kategori KAM sedang dan rendah, sedangkan pada kategori KAM tinggi peningkatan kemampuan berpikir kreatif matematis tidak lebih baik secara signifikan dibandingkan peningkatan kemampuan berpikir kreatif matematis kelas konvensional. 3) Peningkatan kemandirian belajar siswa siswa yang mendapat pembelajaran dengan Accelerated Learning lebih baik daripada yang memperoleh pembelajaran konvensional jika ditinjau secara keseluruhan. 4) Peningkatan kemandirian belajar siswa siswa yang mendapat pembelajaran dengan Accelerated Learning lebih baik daripada peningkatan kemandirian belajar siswa yang memperoleh pembelajaran konvensional pada kategori KAM tinggi, sedang, dan rendah.